Cultural diversity really is like biological diversity: Reply to comments on the nature of religious diversity: A cultural ecosystem approach - Wilson, D; Hartberg, Y; MacDonald, I; Lanman, J; Whitehouse, H (Taylor and Francis, 2016)
Studies of religious and other cultural groups tend to be particularistic or focus on one or more axes of variation. In this article we develop a more comprehensive approach to studying cultural diversity that emulates the study of biological diversity. We compare our cultural ecosystem approach with the axis approach, using the distinction between “tight” and “loose” cultures as an example. We show that while the axis approach is useful, the cultural ecosystem approach adds considerable value to the axis approach. We end by advocating the establishment of field sites for the s